New Creep-Resistant Cast Alloys with Improved Oxidation Resistance in Water Vapor at 650–800°C - Dryepondt, Sebastien; Pint, Bruce A.; Maziasz, Philip J. (Frontiers in Materials, 2015)
Cast stainless steel CF8C-Plus (19wt%Cr/12%Ni) has excellent creep properties, but limited oxidation resistance above 700°C in environments containing H2O. One strategy to improve the alloy oxidation performance is to increase the Cr and Ni concentration. Two new alloys, with, respectively, 21wt%Cr–15wt%Ni and 22wt%Cr–17.5wt%Ni were therefore developed and their long-term oxidation behaviors in humid air were compared with the oxidation behavior of five other cast alloys. At 650°C and 700°C, all the alloys formed internal Cr-rich nodules, and outer nodules or layers rich in Fe and Ni, but they grew a protective Cr-rich inner layer over time. At 750°C, the lower alloyed steels such as CF8C-Plus showed large metal losses, but the two new alloys still exhibited a protective oxidation behavior. The 21Cr–15Ni alloy was severely oxidized in locations at 800°C, but that was not the case for the 22Cr–17.5Ni alloy. Therefore, the two new modified alloys represent a potential operating temperature gain of, respectively, 50°C and 100°C in aggressive environments compared with the CF8C-Plus alloy.